PENGUATAN NILAI PENDIDIKAN LEWAT GAMELAN GANDRUNG DALAM UPACARA PIODALAN NGINGKUP DI PURA TAMAN LIMUT, PENGOSEKAN KELOD, MAS, UBUD, GIANYAR - I Wayan - Sukadana; I Putu Gede Padma Sumardiana -; I Putu Agustana -; Pande Gde Eka Mardiana -; I Komang Gede Sandanu Arta - (UNHI PRESS, 2023)
ABSTRACT Gandrung Gamelan is a Balinese gamelan which is a rare type of gamelan, not many areas in Bali, especially in Gianyar Regency, have Gandrung Gamelan, while several areas in the Gianyar Regency area that have Gandrung Gamelan are Banjar Tegenungan, Banjar Pakuwudan, Banjar Sebali, Susut Traditional Village, and Banjar Pengosekan Kelod. Gandrung Gamelan. Like the Gandrung Gamelan at Taman Limut Temple, Banjar Pengosekan Kelod, this Gandrung Gamelan has a unique instrument, its sacred function, where the Gandrung Gamelan at Taman Limut Temple is performed every time the Piodalan Ngingkup is held. Why is the Gamelan Gandrung tradition in the Ngingkup Ceremony at Taman Limut Temple still carried out and what is its educational value to society? The aim of the research is to explain the educational value contained in the Gandrung gamelan tradition. In this research, a qualitative approach is more appropriate to be developed on the grounds that the data obtained from observations, interviews and document studies are spread across the Pengosekan community area. The discussion in it also involves aesthetic and behaviorist theories. The results of his research found that the presence of Gandrung gamelan for society has educational value as an important form of bond in maintaining ritual life as a form of strengthening the existence of religion. Keywords: gamelan music, educational value, limut garden.